Risk Factors Associated With Postoperative Mortality Among COVID-19 Positive Patients: Results of 3027 Operations and Procedures. Issue 6 (20th December 2022) - Yilmaz, Sumeyye; Sapci, Ipek; Jia, Xue; Argalious, Maged; Taylor, Mark A.; Ridgeway, Beri M.; Haber, Georges-Pascal; Steele, Scott R.
Abstract : Objective: To investigate the predictors of postoperative mortality in coronavirus disease 2019 (COVID-19)–positive patients. Background: COVID-19–positive patients have more postoperative complications. Studies investigating the risk factors for postoperative mortality in COVID-19–positive patients are limited. Methods: COVID-19–positive patients who underwent surgeries/procedures in Cleveland Clinic between January 2020 and March 2021 were identified retrospectively. The primary outcome was postoperative/procedural 30-day mortality. Secondary outcomes were length of stay, intensive care unit admission, and 30-day readmission. Results: A total of 2543 patients who underwent 3027 surgeries/procedures were included. Total 48.5% of the patients were male. The mean age was 57.8 (18.3) years. A total of 71.2% had at least 1 comorbidity. Total 78.7% of the cases were elective. The median operative time was 94 (47.0–162) minutes and mean length of stay was 6.43 (13.4) days. Postoperative/procedural mortality rate was 4.01%. Increased age [odds ratio (OR): 1.66, 95% CI, 1.4–1.98; P <0.001], being a current smoker [2.76, (1.3–5.82); P =0.008], presence of comorbidity [3.22, (1.03–10.03); P =0.043], emergency [6.35, (3.39–11.89); P <0.001] and urgent versus [1.78, (1.12–2.84); P =0.015] elective surgery, admission through the emergency department [15.97, (2.00–127.31); P =0.009], or inpatient service [32.28, (7.75–134.46); P <0.001] versus outpatients were associated with mortality in the multivariable analysis. Among all specialties, thoracic surgery [3.76, (1.66–8.53); P =0.002] had the highest association with mortality. Total 17.5% of the patients required intensive care unit admission with increased body mass index being a predictor [1.03, (1.01–1.05); P =0.005]. Conclusions: COVID-19–positive patients have higher risk of postintervention mortality. Risk factors should be carefully evaluated before intervention. Further studies are needed to understand the impact of pandemic on long-term surgical/procedural outcomes.